Physician Assistant and Nurse Practitioner Malpractice Trends. (October 2017) - Brock, Douglas M.; Nicholson, Jeffrey G.; Hooker, Roderick S.
Trends in malpractice awards and adverse actions (e.g., revocation of provider license) following an act or omission constituting medical error or negligence were examined. The National Practitioner Data Bank was used to compare rates of malpractice reports and adverse actions for physicians, physician assistants (PAs), and nurse practitioners (NPs). During 2005 through 2014, there ranged from 11.2 to 19.0 malpractice payment reports per 1, 000 physicians, 1.4 to 2.4 per 1, 000 PAs, and 1.1 to 1.4 per 1, 000 NPs. Physician median payments ranged from 1.3 to 2.3 times higher than PAs or NPs. Diagnosis-related malpractice allegations varied by provider type, with physicians having significantly fewer reports (31.9%) than PAs (52.8%) or NPs (40.6%) over the observation period. Trends in malpractice payment reports may reflect policy enactments to decrease liability.